2001
DOI: 10.1002/ffj.957
|View full text |Cite
|
Sign up to set email alerts
|

Sarisan from leaves ofPiper affinis hispidinervum C. DC (long pepper)

Abstract: The essential oil obtained from the leaves of Piper affinis hispidinervum C. DC was analysed by GC-MS. Sixteen substances were identified, corresponding to 98.9% of the oil. The major component (74.3%) was sarisan (1-allyl-2-methoxy-4,5-methylenedioxybenzene), identified by NMR spectroscopy. Safrole (18.4%) was also found in the oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
1
16
1
1
Order By: Relevance
“…Piper aduncum and P. marginatum presented compounds already reported as insecticides in previous works, such as dillapiol, asaricine (sarisan), piperitone and myristicin (Bizzo et al, 2001;Morais et al, 2007;Qin, Huang, Li, Chen, & Peng, 2010;Souto et al, 2012;Santana et al, 2015;Ribeiro, Camara, & Ramos, 2016;Krinski & Foerster, 2016). For P. caldense, P. fuligineum, P. Mollicomum, and P. mosenii, there are no studies regarding the insecticidal activity, and our work is the first to test the ovicidal activity against a lepidopteran pest of importance in Brazilian agriculture.…”
Section: Discussionmentioning
confidence: 98%
“…Piper aduncum and P. marginatum presented compounds already reported as insecticides in previous works, such as dillapiol, asaricine (sarisan), piperitone and myristicin (Bizzo et al, 2001;Morais et al, 2007;Qin, Huang, Li, Chen, & Peng, 2010;Souto et al, 2012;Santana et al, 2015;Ribeiro, Camara, & Ramos, 2016;Krinski & Foerster, 2016). For P. caldense, P. fuligineum, P. Mollicomum, and P. mosenii, there are no studies regarding the insecticidal activity, and our work is the first to test the ovicidal activity against a lepidopteran pest of importance in Brazilian agriculture.…”
Section: Discussionmentioning
confidence: 98%
“…For example, myristicin, present at 3.6% in the tested EO, sarisan (BIZZO et al, 2001) or safrole (HUANG et al, 1999), all of which have a methylenedioxyphenyl group in their structure are natural insecticides that could be the target of such association. Brazão et al (2014), when assessing the EO extracted from P. aduncum against susceptible and resistant isolates of Staphylococcus spp., also showed the combined bactericidal action of dillapiole and myristicin (1 to 2%), lending further support to our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…For identification, the unknown compound was isolated by CC on silica gel and eluted with hexane-ethyl acetate mixtures. After 1 H and 13 CNMR studies, it was identified as sarisan (Bizzo et al, 2001). …”
Section: Monoterpenes and Sesquiterpenes (Plant Volatiles)mentioning
confidence: 99%